2013
DOI: 10.1177/0961203313512881
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and incidence of Systemic Lupus Erythematosus (SLE) in selected cities from three Commonwealth of Independent States countries (the Russian Federation, Ukraine and Kazakhstan)

Abstract: We assessed the prevalence and incidence of Systemic Lupus Erythematosus (SLE) in 2010 in adults from four cities in Russia, Kazakhstan and Ukraine. Individuals with SLE were identified retrospectively from the medical records of specialized centers. Prevalent SLE patients were nondeceased city residents, diagnosed prior to December 31, 2010; incident patients were residents newly diagnosed between January 1 and December 31, 2010. Population size was obtained from official census data. The observed prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 13 publications
1
19
0
6
Order By: Relevance
“…Сле-довательно, с большой долей вероятности можно утвер-ждать, что у достаточно большого количества больных забо-левание остается недиагностированным или диагноз уста-новлен неправильно. Это также может объяснять низкую распространенность (по установленному диагнозу) СКВ, о чем сообщалось в нашей предыдущей публикации [12].…”
Section: д е м о г р а ф и ч е с к и е к л и н и ч е с к и е и л а unclassified
See 2 more Smart Citations
“…Сле-довательно, с большой долей вероятности можно утвер-ждать, что у достаточно большого количества больных забо-левание остается недиагностированным или диагноз уста-новлен неправильно. Это также может объяснять низкую распространенность (по установленному диагнозу) СКВ, о чем сообщалось в нашей предыдущей публикации [12].…”
Section: д е м о г р а ф и ч е с к и е к л и н и ч е с к и е и л а unclassified
“…Данные этого иссле-дования позволяют получить представление о заболеваемо-сти и распространенности СКВ [12].…”
unclassified
See 1 more Smart Citation
“…According to pooled results from epidemiological trials conducted in Europe and the United States in 1950-2006, the average prevalence of SLE was about 50 per 100,000 population [1]. In Russia, according to epidemiological studies conducted in Yaroslavl and Kursk, it was shown that the prevalence of SLE in these regions is about 9 per 100,000 population which is much less than in Europe [18]. Currently, an increase in SLE incidence is being recorded, which is thought to be associated with improvement in rheumatic diseases detection [5].…”
Section: Introductionmentioning
confidence: 99%
“…7 An Australian survey found a prevalence of 95 per 100,000 in the indigenous peoples compared with 45 per 100,000 in the non-indigenous population. 8 In addition, with this higher prevalence in certain ethnic groups, there was frequent evidence of more serious disease.…”
mentioning
confidence: 97%